Fast Nanoliter‐Scale Cell Assays Using Droplet Microarray–Mass Spectrometry Imaging. Issue 3 (9th February 2021) - RamalloGuevara, Carina; Paulssen, Dorothea; Popova, Anna A.; Hopf, Carsten; Levkin, Pavel A.
Abstract: In pharmaceutical research and development, cell‐based assays are primarily used with readout that rely on fluorescence‐based and other label‐dependent techniques for analysis of different cellular processes. Superhydrophobic–hydrophilic droplet microarrays (DMA) and matrix‐assisted laser desorption/ionization (MALDI) mass spectrometry (MS) have recently emerged as key technologies for miniaturized high‐throughput cell assays and for label‐free molecular high‐content drug profiling, respectively. Here, nanoliter‐scale cell assays are integrated on DMAs with MALDI–MS imaging (MALDI–MSI) approaches to a droplet microarray–mass spectrometry imaging (DMA–MSI) platform. Using A549 lung cancer cells, concentration‐response profiling of a pharmaceutical compound, the fatty acid synthase inhibitor GSK2194069, are demonstrated. Direct cell culture on DMAs enables combination of microscopy and high speed, high molecular content analysis using MALDI–MSI. Miniaturization of array spots down to 0.5 mm confining 40 nL droplets allows for MALDI imaging analysis of as few as ten cells per spot. Partial automation ensures a fast sample preparation workflow. Taken together, the integrated DMA–MSI platform that combines MALDI‐MSI, as a label‐free analytical readout, with the miniaturized droplet microarray platform is a valuable complement to high throughput cell‐based assays technologies. Abstract : Cell‐based assays are crucially important for fundamental research and drug discovery. In this paper the miniaturized droplet microarray platform is combined, as a high‐throughput nanoliter‐scale cell screening technology, with the MALDI‐MS imaging, as a label‐free molecular high‐content analytical readout technology.